Relations between the Central-European Trade Routes and Revenues of EU Members - Miklós Gábor (II. RFKMF, 2024)
Abstract. The Europe – Asia trade relations have been getting more intensive even if the global economy has had to face with the problems and post-effects of COVID19 or the current wars in different regions. It also means for the countries and participants to find new routes for trade – including the freight trains and giant container vessels – in order to avoid the hot and dangerous straits and points. Of course, new trade routes will be related to new economic and financial interests in one hand, on other hand there will be some classic trade countries or big cities, regions which lose their previous weight and importance [1, p.11] This research highlights the shifting of the trade routes and economic geographic process [2, p.68]. What kind of impacts are there in EU countries that a significant part of EU-Chine trade has been moving from vessels to freight trains or to combined, overland-maritime transportation. It has partly taken out the former China – Rotterdam/Hamburg maritime way.
A közép-európai kereskedelmi útvonalak és az EU-tagállamok bevételei közötti kapcsolatok rendszerek
Взаємозв'язок між центральноєвропейськими торговими шляхами та доходами держав-членів ЄС
Keywords: global economy; Trade Route